2020
DOI: 10.1002/adfm.202007356
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Based Sorbents for Multipollutants Removal in Water: A Review of Recent Progress

Abstract: The coexistence of multiple toxic water pollutants (heavy metals, organic dyes, oils, and organic solvents) limits the sustainable supply of clean water worldwide and urges the development of advanced water purification technology that can remove these contaminants simultaneously. Since its discovery, graphene‐based materials have gained substantial attention toward development of new‐generation sorbents for water purification. Despite several recently published reviews on water purification technology using g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 108 publications
(150 reference statements)
0
41
0
Order By: Relevance
“…The exclusive skeleton structure can give the products several especial advantages while also avoiding the agglomeration of particles. [102,103] Since the excellent performance in sewage treatment, seawater desalination, and antibacterial and antifouling materials, extensive attention has been paid to MOF composites in recent years.…”
Section: Other Mof Compositesmentioning
confidence: 99%
“…The exclusive skeleton structure can give the products several especial advantages while also avoiding the agglomeration of particles. [102,103] Since the excellent performance in sewage treatment, seawater desalination, and antibacterial and antifouling materials, extensive attention has been paid to MOF composites in recent years.…”
Section: Other Mof Compositesmentioning
confidence: 99%
“…Because of their intrinsic hydrophobicity, low density, and stable chemical bonds, carbon-based materials have long attracted interest as potential oil sorbent materials. CC bonds have a strong covalent interaction with sp 2 hybridization in typical carbon allotropies, including CNT (1-dimension), [143][144][145] graphene (2-dimension), [146][147][148] and graphite (3-dimension). [149,150] These stable carbon structures can be added to existing sorbents to increase their hydrophobicity or improve their oil/ water separation qualities.…”
Section: Carbon-based Sorbentmentioning
confidence: 99%
“…where KF represented to the constant model, [MB]aq,e was the methylene blue concentration in the solution at the equilibrium, and nF represented a value which indicates if the process is favorable (nF greater than 1) or not. The experimental data derived from the adsorption of methyl orange indicated that, the linearized form of the Langmuir isotherm best fitted them: (3) in this equation, KL represented the model constant, and the subscript ad,m represented the maximum dye concentration in the adsorbent. This adsorbent had adsorption uptakes of 244 mg/g and 205 mg/g for methyl orange and methylene blue, respectively.…”
Section: Adsorptionmentioning
confidence: 99%
“…The importance of these adsorptive methodologies on the removal of organic dyes from waters is reflected in the number of investigations and reviews published along the years. Recently, several reviews about the use of a given type of adsorbents in this role, included silica-based mesoporous materials of the M41S and SBA-n families [1], different types of graphene-based materials [2,3], biochars [4], metal-organic frameworks (MOF) [5,6], various types of polymeric nanofibers [7], metal-doped porous carbon materials [8], and activated carbon fibers [9] The present work reviews very recent publications (first half of 2021 year) about the use of adsorbents in the removal of organic dyes from waters, in many cases, the investigations are carried out on synthetic solutions, but there are some examples in which adsorbents are used on real waters. Readers must be aware that this review does not include publications about desorption-degradation processing of these toxic chemicals.…”
Section: Introductionmentioning
confidence: 99%